Does ambulation modify venous thromboembolism risk in acutely ill medical patients? - Amin, Alpesh N.; Girard, Frederick; Samama, Meyer M. (Thrombosis and Haemostasis, 2010)
In the US, ambulatory status is often a criterion for stopping prophylaxis for venous thromboembolism (VTE). In an analysis of the prophylaxis in MEDical patients with ENOXaparin (MEDENOX) trial, ambulatory status was assessed as outcome and patients grouped accordingly for further analysis. Rates of VTE and bleeding were evaluated. Using multivariate logistic regression, the relationships between thromboprophylaxis, VTE risk, and ambulatory status were assessed. Ambulatory status was reached in 607/1,084 patients, in a mean time of 4.4 days. Thromboprophylaxis was provided for 7.3 and 7.7 days in the ambulatory and non-ambulatory groups. Although VTE rates were lower in ambulatory patients, enoxaparin 40 mg once daily significantly reduced the risk of VTE vs. placebo in ambulatory (3.3% vs. 10.6%; relative risk [RR] = 0.31; 95% confidence interval [CI], 0.13ﺹ0.78; p=0.008) and non-ambulatory patients (9.0% vs. 19.7%; RR = 0.46; 95% CI, 0.23ﺹ0.91; p=0.02). Major bleeding was not significantly different between enoxaparin and placebo in either group. By multivariate regression analysis, VTE risk in ambulatory patients was lower with enoxaparin vs. placebo (odds ratio [OR] = 0.28; 95% CI, 0.11ﺹ0.74; p=0.01), but higher in patients with a history of VTE (OR = 3.74; 95% CI, 1.59ﺹ8.84; p=0.003) or cancer (OR = 2.12; 95% CI, 1.00ﺹ4.48; p=0.049). Despite timely mobilisation, patients who become ambulatory are at VTE risk and experience a significant risk reduction with enoxaparin 40 mg. Therefore, it is essential that ambulatory patients receive recommended thromboprophylaxis.
Keywords: Ambulation; enoxaparin; thromboprophylaxis; venous thromboembolism